Tren Publikasi Manuskrip Daun Lontar Dalam Preservasi Pengetahuan (2014–2024) - Saif Haromain Al Fashli; Tamara Adriani Salim (Pusat Publikasi Ilmiah UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to analyze the trends and development of scientific publications on palm leaf manuscripts within the context of knowledge preservation, based on data indexed in the Scopus database from 2014 to 2024. The research employs bibliometric analysis with the support of VOSviewer software to visualize keyword networks, productive journals, and country distribution. The results indicate a total of 168 documents on this topic, with India ranking as the most productive country, followed by Indonesia with 23 publications. Restaurator is identified as the journal with the highest number of contributions. Keyword cluster visualization reveals that research on palm leaf manuscripts has developed through various multidisciplinary approaches, including philology, cultural conservation, and the application of digital technologies such as script recognition and image processing. These findings affirm that knowledge preservation encompasses not only the physical conservation of manuscripts but also the safeguarding of their content, cultural values, and contextual significance. Therefore, Indonesia’s scholarly contribution should be further enhanced through interdisciplinary collaboration and institutional capacity building to support the sustainable preservation and utilization of local manuscripts.